The sundae scoop - Murphy, Stuart J., 1942- (Murphy, Stuart J., 1942- MathStart., 2003)
At the picnic on the last day of school, James, his friends, and the cafeteria lady make a variety of ice cream sundaes, using mathematics to figure out how many different kinds they can create.